English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

find the mistake
let A = B
A squared - B squared = AB- B squared
(A+B)(A-B)= B(A-B)
A+B=B
B+B=B
2B=B
2=1

2007-05-13 14:15:21 · 4 answers · asked by sam8502005 1 in Science & Mathematics Mathematics

4 answers

(A+B)(A-B)= B(A-B)
A+B=B

Given that A=B
A-B=0
You are dividing by 0 which is not allowed.

2007-05-13 14:18:40 · answer #1 · answered by gudspeling 7 · 1 0

If a=b, then the first line is incorrect. A squared- B squared (or A squared, since A and B or equal)= 0. The 0 would be on the left side of the equation, not the (A+B)(A-B). That makes no sense.

2007-05-13 21:27:30 · answer #2 · answered by cakeeater0119 5 · 1 0

you can't divide by A-B as you did in the 3rd step because A-B = 0

2007-05-13 21:34:56 · answer #3 · answered by Kathleen K 7 · 1 0

It´s always the same stupid thing
As you divide by (A-B) you are dividing by zero and this is not allowed.Please don´t insist with the same stupidity

2007-05-13 21:20:16 · answer #4 · answered by santmann2002 7 · 1 1

fedest.com, questions and answers